Current Practices and Opportunities in a Resident Clinic Regarding the Care of Older Adults with Multimorbidity - Schoenborn, Nancy L. (J Am Geriatr Soc, 2015)
OBJECTIVES: Multimorbidity (≥2 chronic conditions) affects more than half of all older adults. The American Geriatrics Society developed and published guiding principles for the care of older adults with multimorbidity in 2012. Improved clinician training in caring for older adults with multimorbidity is needed, but it is not clear what opportunities arise within clinical encounters to apply the guiding principles or how clinicians at all stages of training currently practice in this area. This project aimed to characterize current practice and opportunities for improvement in an internal medicine residency clinic regarding the care of older adults with multimorbidity. DESIGN: Qualitative content analysis of audio-recorded clinic visits. SETTING AND PARTICIPANTS: Thirty clinic visits between 21 internal medicine residents and 30 of their primary care patients aged 65 and older with two or more chronic conditions were audio-recorded. Patients’ mean age was 73.6, and they had on average 3.7 chronic conditions and took 12.6 medications. MEASUREMENTS: Transcripts of the audio-recorded visit discussions were analyzed using standard techniques of qualitative content analysis to describe the content and frequency of discussions in the clinic visits related to the five guiding principles: patient preferences, interpreting the evidence, prognosis, clinical feasibility, and optimizing therapies. RESULTS AND CONCLUSIONS: All visits except one included discussions that were thematically related to at least one guiding principle, suggesting regular opportunities to apply the guiding principles in primary care encounters with internal medicine residents. Discussions related to some guiding principles occurred much more frequently than others. Patients presented a number of opportunities to incorporate the guiding principles that the residents missed, suggesting target areas for future educational interventions.